Pest survey card on Anastrepha ludens. Issue 1 (29th January 2021) - ,; Mertens, Jan; Schenk, Martijn; Delbianco, Alice; Graziosi, Ignazio; Vos, Sybren
Abstract : This pest survey card was prepared in the context of the EFSA mandate on plant pest surveillance (M‐2020‐0114), at the request of the European Commission. Its purpose is to guide the Member States in preparing data and information for surveys of the Mexican fruit fly Anastrepha ludens .These are required to design statistically sound and risk‐based pest surveys, in line with current international standards. Anastrephaludens is a clearly defined taxonomic entity, but identification of this fruit fly is challenging as several species within the genus are morphologically similar to and may co‐exist with A. ludens . Imports of citrus fruits and fruits of several tropical hosts are subject to specific measures in EU aiming to prevent entry ofnon‐European Tephritidae.Nevertheless, the most likely introduction of A. ludens would be via the transport of infested fruit followed by natural spread, whichmight be facilitated by the fact that the species is considered a strong flier. The insect is currently absent from the EU and surveys should aim at substantiating pest freedom. Adult trapping using food‐based attractants is the preferred survey method for the detection of the fly.Surveillance should preferably be executed during the time of the season in whichfruits from the main host plants are available and abundant and the climate conditions are favourable. Anastrephaludens is a polyphagous species. The primary host for detection surveys in the EU would be cultivated Citrus spp., whereas other host species should be includedfor delimiting surveys. The pestis expected to be able to establish in the most southern part of the EU.Species‐levelidentification of A.ludens requires morphological examination of the ovipositor and especially the aculeustip of females. The updated pest survey card for Anastrepha ludens is published and available online in the EFSA Plant Pest Survey Cards Gallery at the following link: https://arcg.is/vqjqr